The acquisition of Malay plural marking among International students of International Islamic University Malaysia. - Hazalan Haffiz, Nur Amirah; Mohamed Salleh, Rabiah Tul Adawiyah (2020)
Processability Theory (Di Biase, Kawaguchi, & Yamaguchi, 2015; Pienemann, 1998) is a current psycholinguistics theory designed to investigate the development of second language acquisition among language learners. This theory has been tested on many second language learning, such as English (Pienemann, 1998), Swedish (Pienemann & Håkansson, 1999), Japanese (Kawaguchi, 2015), and Italian (Di Biase & Bettoni, 2015), among others. However, based on our knowledge, studies investigating the development of Malay as a foreign language using Processability theory have not been conducted yet. Therefore, this study aims to investigate the development of Malay as a foreign language, particularly looking at how Malay plural marking structures develop in these learners. The participants of this study will be 4 international students studying at International Islamic University Malaysia (IIUM). All of them are enrolled in the beginner level of Malay language class (Level 1). The Malay class is conducted twice a week for 4 months (one semester). The participants will be tested twice; at T1 (pre-test) in week 9 of the semester and at T2 (post-test), in week 14. The data will be elicited from picture elicitation task and cloze test. The findings of this study are expected to cast some light on the acquisitional process of Malay plural marking structures by Malay foreign language learners. The findings will also widen Processability Theory typological range of application to a language such as Malay, which belongs to the Austronesian family (Dryer & Haspelmath, 2013).